A bibliometric analysis of the International Journal of Islamic and Middle Eastern Finance and Management. Issue 4 (1st March 2021) - Özdemir, Mücahit; Selçuk, Mervan
Abstract : Purpose: The purpose of this paper is to indicate the current state of studies on Islamic finance and management through a bibliometric analysis of the only social science citation index (SSCI)-indexed journal in this field. Design/methodology/approach: The paper uses a bibliometric analysis, collecting data from the 319 papers published in the International Journal of Islamic and Middle Eastern Finance and Management (IMEFM) from 2008 to 2019. Moreover, VOSviewer software has been used to illustrate the citation analysis (including most cited papers, most cited authors and authors' affiliated institutions and countries) and the keyword map. Findings: The number of papers published in each issue of the IMEFM is found to have significantly increased owing to its unique situation being the only SSCI-indexed journal in this domain. The share of the empirical researches in total papers published annually has steadily risen, reaching 95% in 2019. In terms of case countries, although Malaysia is the most examined country in the papers, other countries such as Indonesia and Turkey are found to have been used as a case country by researchers recently. Islamic banking-related papers are the most prevalent studies, as expected, with mainly their performance being examined. Meanwhile, the number of papers about Islamic social financial institutions has notably grown in recent years. Finally, technology-based initiatives such as crowdfunding and cryptocurrencies are noted to have not yet been the subject of any paper. Originality/value: The main contribution of this study is its analysis of the only SSCI-indexed journal on Islamic finance and management using bibliometrics. Also, all the papers published in the journal have been reviewed in terms of methodology, case country/country groups and topics/subtopics to lead the way for future research.